High-performance removal of radionuclides by porous organic frameworks from the aquatic environment: A review. (November 2021) - Gendy, Eman Abdelnasser; Oyekunle, Daniel Temitayo; Ali, Jawad; Ifthikar, Jerosha; El-Motaleb Mosad Ramadan, Abd; Chen, Zhuqi
Abstract: Dealing with unwanted nuclear waste is still a serious issue from the point of view of humans and the environment because of its harmful and dangerous effects. Recently, porous organic frameworks (POFs) have gained an increasing concern as effective materials in the removal of various types of hazardous metal ions, especially radioactive metal ions. POFs are a unique class that included covalent organic frameworks (COFs) and metal-organic frameworks (MOFs) with strong covalent bonds, large surface area, high adsorption capacity, tunable porosity, and a porous structure with more efficient than conventional adsorbents. This review highlights the recent developments of POFs for the rapid elimination of radionuclide. The unique characteristics, adsorption properties, and interaction mechanisms between radioactive metal ions and the POF-based materials are summarized. Also, prospects for enhancing the performance of POFs to capture radioactive metal ions are discussed. Graphical abstract: Image 1 Highlights: Porous organic frameworks (POFs) are superior adsorbents in eliminating radionuclides. Unique characteristics and adsorption properties of POFs are summarized. Recent developments of POFs for capture radionuclides are highlighted. A comparison between POF-based materials and other adsorbents is discussed.